(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Putra AW, Priawandiputra W, Litaay M, Atmowidi T. 2022. Comparison of shallow water soft coral (Octocorallia) diversity and distribution among three islands in Makassar Strait, Indonesia. Biodiversitas 23: 5951-5961. There are only a few soft coral research in Indonesia. In the last ten years, there has been only seven published research. On the other hand, there are still many areas that are still unexplored, and every unexplored location has a chance to find a new species, thus we did this research. This study aims to conduct biodiversity research in the selected areas where soft corals biodiversity papers have never been published before. The distribution of soft coral in three small islands in Makassar strait and close to Sulawesi main island is reported in this paper. We hope that there is a correlation between the soft coral community in each researched island. The research was done by using a modified visual census method with 50 meters transect in the shallow water area (approx. 5 meters in depth). The data was collected by diving, sampling, and capturing images of each species found. Identification was made by comparing morphological characteristics using the book soft coral and Sea fans by Fabricius and Alderslade and newest papers about soft coral. In total, there are 41 species belonging to 14 genera and eight families found in this research. There is not much correlation between these three islands’ soft coral communities. Every island had its key species based on the characteristics of the underwater habitats. The genera Acrossota and Dendronephtya only occur in Barrang Caddi Island, while, Cladiella, Clavularia and Xenia were only found in Gusung Toraja Island, and Anthellia and Heteroxenia were only found in Pannikiang Island. The genera Litophyton, Lobophytum, Sarcophyton, and Sinularia were found in all three researched islands. The south side of every island has the highest species abundance compared to the North, West, and Eastside.